2016
DOI: 10.1007/s11606-016-3591-8
|View full text |Cite
|
Sign up to set email alerts
|

The Modified, Multi-patient Observed Simulated Handoff Experience (M-OSHE): Assessment and Feedback for Entering Residents on Handoff Performance

Abstract: BACKGROUND: Despite the identification of transfer of patient responsibility as a Core Entrustable Professional Activity for Entering Residency, rigorous methods to evaluate incoming residents' ability to give a verbal handoff of multiple patients are lacking. AIM: Our purpose was to implement a multi-patient, simulation-based curriculum to assess verbal handoff performance. SETTING: Graduate Medical Education (GME) orientation at an urban, academic medical center. PARTICIPANTS: Eighty-four incoming residents … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
33
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(37 citation statements)
references
References 23 publications
(27 reference statements)
3
33
0
Order By: Relevance
“…Previous studies reported that simulation is an effective way to teach handoffs. 4,5,11 However, most evaluated a 1-year experience. Our study evaluated a handoff training program over 3 years and demonstrated continued compliance with I-PASS by evaluating handoff documents throughout the year.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies reported that simulation is an effective way to teach handoffs. 4,5,11 However, most evaluated a 1-year experience. Our study evaluated a handoff training program over 3 years and demonstrated continued compliance with I-PASS by evaluating handoff documents throughout the year.…”
Section: Discussionmentioning
confidence: 99%
“…Several residency programs developed curricula to teach handoffs using I-PASS, and many used simulation to assess residents' skills. These innovations led to improved knowledge 4,5 ; however, there is limited postintervention data on changes in handoff practice. 6,7 Additionally, as entrustable professional activities are incorporated into medical school training, including handoffs, the role of teaching handoff skills to interns as they begin residency is unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Previous reviews of the clinical handover literature have concluded that, although considerable attention has been directed to researching and implementing improved care transition processes, this has not yet led to a clear articulation of best practices. Current handover practices are therefore not as robust or efficient as they might be, thus presenting a significant risk to patient safety . In addition, systems factors, such as increased handovers for patient care resulting from mandated restrictions in duty hours for junior doctors, have led to more opportunities for errors …”
Section: Introductionmentioning
confidence: 99%
“…Current handover practices are therefore not as robust or efficient as they might be, thus presenting a significant risk to patient safety. 1,2,4,5 In addition, systems factors, such as increased handovers for patient care resulting from mandated restrictions in duty hours for junior doctors, have led to more opportunities for errors. 1,2,6,7 Communication skills training is frequently proposed as a way to improve handover safety and efficiency, which in turn has led to the development of various tools to assist structured dialogue between clinicians about a patient's status.…”
Section: Introductionmentioning
confidence: 99%
“…With this format, information is provided and skills are assessed of all incoming first-year residents during their on-boarding process. [3][4][5] Implementing a safe opioid module with accompanying OSCE during intern orientation would allow for delivery to a larger audience, resulting in a more effective impact on turning the tide on this epidemic.…”
mentioning
confidence: 99%